The role of opportunistic pathogens as etiological agents of intrauterine infections - V. V. Kosenchuk; T. N. Rybalkina; R. E. Boshyan; N. V. Karazhas; M. N. Kornienko; P. A. Veselovsky; M. Yu. Lysenkova; M. S. Savenkova; M. Yu. Ivanova (Детские инфекции (Москва))
The study showed a high prevalence of markers of herpesvirus infections among mothers — from 71% to 98% of HSV, EBV and CMV infections and from 29% to 58% of HHV-6 infection. HSV remains the most common etiological agent of intrauterine infections among herpesviruses — markers of active infection caused by this virus were found in 28.3% samples. The difficulty of determining the source of infection in the absence of data in the early stages of pregnancy is presented on 4 out of 10 cases of active HHV-6 infection. Markers of active pneumocystic infection were detected only in mothers: in the group with children under the age of 21 days — in 21—27% of cases, with children aged 22 to 28 days — in 15—21%. In addition to non-specific multiple organ failure during intrauterine infections (26.3%), only one organ system was observed: hypoxic-hemorrhagic lesions of the central nervous system were diagnosed more often — 17%, as well as meningitis/encephalitis, or hepatitis, or pneumonia, or disorders of hematopoiesis, or rash. In 17.5% of children from the comparison group, i.e. without any clinical manifestations of intrauterine infections, markers of active herpes virus infections were detected.